2018
DOI: 10.1080/15368378.2018.1471700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weak combined static and extremely low-frequency alternating magnetic fields on spatial memory and brain amyloid-β in two animal models of Alzheimer’s disease

Abstract: Subchronic effect of a weak combined magnetic field (MF), produced by superimposing a constant component, 42 µT and an alternating MF of 0.08 µT, which was the sum of two frequencies of 4.38 and 4.88 Hz, was studied in olfactory bulbectomized (OBE) and transgenic Tg (APPswe, PSEN1) mice, which were used as animal models of sporadic and heritable Alzheimer's disease (AD) accordingly. Spatial memory was tested in a Morris water maze on the following day after completion of training trials with the hidden platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
1
6
0
1
Order By: Relevance
“…In the present study, OBX rats displayed a significantly increased hyperemotionality score when experiencing four mild stimuli. Similarly to previous studies [23,24], we observed that OBX rats exhibited significantly prolonged escape latencies on day 3 and day 5 in the MWM navigation test, and shortened time and movement distance percentage in the target quadrant in the probe test, which indicates the spatial memory deficits in OBX rats. Chronic fluoxetine treatment relieved the hyperemotional response, but could not ameliorate impairment in learning and memory in OBX rats.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, OBX rats displayed a significantly increased hyperemotionality score when experiencing four mild stimuli. Similarly to previous studies [23,24], we observed that OBX rats exhibited significantly prolonged escape latencies on day 3 and day 5 in the MWM navigation test, and shortened time and movement distance percentage in the target quadrant in the probe test, which indicates the spatial memory deficits in OBX rats. Chronic fluoxetine treatment relieved the hyperemotional response, but could not ameliorate impairment in learning and memory in OBX rats.…”
Section: Discussionsupporting
confidence: 88%
“…Влияние, оказываемое КНЧ на нейродегенеративные заболевания, описано Benassi et al [13] на примере болезни Паркинсона, когда было отмечено значительное ухудшение окислительно-восстановительного потенциала и содержания тиола в клетках SH-SY5Y, а также рост карбонилирования белков. Подобные явления описывались Bobkova et al [14], которые отметили изменения в пространственной памяти и мозговом амилоиде-β на двух животных моделях с заболеванием Альцгеймера. В обзоре Terzi et al [15] суммированы добавочные нейродегенеративные эффекты.…”
unclassified
“…Carruba et al [12] demonstrated experimentally that low-frequency pulse by mobile phones triggered EEG evoked potentials in human volunteers. Effects produced by ELF on neurodegenerative diseases were shown by Benassi et al [13] regarding Parkinson's disease, with significantly impaired redox homeostasis and thiol content in SH-SY5Y cells, and an increase in protein carbonylation; and by Bobkova et al [14] with changes in spatial memory and brain amyloid-β in two animal models of Alzheimer's disease. A review by Terzi et al [15] summarizes additional neurodegenerative effects.…”
mentioning
confidence: 99%